A protocol developing, disseminating, and implementing a core outcome set for infertility - Duffy, J; Bhattacharya, S; Curtis, C; Evers, J; Farquharson, R; Franik, S; Legro, R; Lensen, S; Mol, B; Niederberger, C; Ng, E; Repping, S; et al. (Oxford University Press, 2018)
Study Questions We aim to produce, disseminate, and implement a core outcome set for future infertility research. What is known already Randomised controlled trials evaluating infertility treatments have reported many different outcomes, which are often defined and measured in different ways. Such variation contributes to an inability to compare, contrast, and combine results of individual randomised trials. The development of a core outcome set will ensure outcomes are consistently collected and reported across future pre-eclampsia research. Study design, size, duration This is a consensus study using the modified Delphi method. All stakeholders, including healthcare professionals, allied healthcare professionals, researchers, people with lived experience of infertility will be invited to participate. Participants, setting methods An international steering group, including people with lived experience of infertility, healthcare professionals, allied healthcare professionals, and researchers, has been formed to guide the development of this core outcome set. Potential core outcomes have been identified through a comprehensive literature review of randomised controlled trials evaluating treatments for infertility and will be entered into a modified Delphi method. Participants will be asked to score potential core outcomes on a nine-point Likert scale anchored between one (not important) and nine (critical). Repeated reflection and rescoring should promote convergence towards consensus ‘core’ outcomes. We will establish standardised definitions and recommend high-quality measurement instruments for individual core outcomes.